Summary of household baseline survey results: Lushoto, Tanzania - Lyamchai, Charles; Yanda, P.Z.; Sayula, George; Kristjanson, Patricia M. (2011)
This report summarizes the results of a baseline household-‐level survey, led by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), carried out in 7 villages and 140 households in Lushoto, Tanzania in January 2011. The objective of this baseline effort was to describe the characteristics of the farming systems found across a wide range of research sites in 12 countries, including the Lushoto site, and to better understand what kinds of farming practice changes households have been making and why.